2018
DOI: 10.1007/s11099-017-0696-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iron, zinc and manganese shortage-induced change on photosynthetic pigments, some osmoregulators and chlorophyll fluorescence parameters in lettuce

Abstract: Although the beneficial role of Fe, Zn, and Mn on many physiological and biochemical processes is well established, effects of each of these elements on chlorophyll (Chl) a fluorescence and photosynthetic pigment contents is not well studied. The objective of this study was to evaluate effects of Fe, Zn, and Mn deficiency in two lettuce cultivars. The parameters investigated could serve also as physiological and biochemical markers in order to identify stress-tolerant cultivars. Our results indicated that micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 51 publications
(60 reference statements)
6
43
0
3
Order By: Relevance
“…Quality parameters were also influenced by the sediment. Lettuce soluble sugar content is relatively low in comparison with other plant species (about 3 g 100 g −1 FW); nevertheless, they are important as a source of energy for maintaining cell metabolism and for their role in osmoregulation . After harvest, sugars are essential for keeping cells alive and to ensure a long shelf life of the final product .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Quality parameters were also influenced by the sediment. Lettuce soluble sugar content is relatively low in comparison with other plant species (about 3 g 100 g −1 FW); nevertheless, they are important as a source of energy for maintaining cell metabolism and for their role in osmoregulation . After harvest, sugars are essential for keeping cells alive and to ensure a long shelf life of the final product .…”
Section: Discussionsupporting
confidence: 89%
“…Lettuce soluble sugar content is relatively low in comparison with other plant species (about 3 g 100 g −1 FW); 26 nevertheless, they are important as a source of energy for maintaining cell metabolism and for their role in osmoregulation. 29 After harvest, sugars are essential for keeping cells alive and to ensure a long shelf life of the final product. 30 In this study, lettuce sugar concentration was in accordance with those reported by Tesi 26 and Mou 31 and was not affected by the growing medium (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Dalam penelitian ini, tidak ada perbedaan komposisi nutrisi AB Mix yang digunakan selama kultivasi bayam maupun selada pada ketiga jenis media tanam. Kadar klorofil dapat berbeda secara signifikan apabila komposisi nutrisi hidroponik dijadikan sebagai parameter atau peubah bebas, terutama unsur N (nitrogen) (Warganegara et al, 2015;Wen et al, 2019), S (sulfur) (Skudra & Ruza, 2017), Fe (besi), Zn (seng), dan Mn (mangan) (Roosta et al, 2018).…”
Section: Hasil Dan Pembahasanunclassified
“…3; Table 2), suggesting that these metabolites, and thereby defence mechanisms of cucumber, are associated with the Si-affected improvement in Fe and Mn availability towards photosynthetic organs. These micronutrients are of importance for photosynthesis and can act as a cofactor for enzymes involved in pathways producing photosynthetic pigments (Roosta et al 2018).…”
Section: Discussionmentioning
confidence: 99%